The Pragmatic Strategies of Impoliteness Within Instagram Comment Sections (On The Discourse Surrounding Prabowo Subianto’s Speeches During The 2024 Political Cycle) - Andreka Septiawan; Jihan Alayya; Tyara Ramadhani Safitri; Zahra Nurhaliza (Indo Publishing, 2025)
This study investigates the pragmatic strategies of impoliteness within Instagram comment sections, focusing on the discourse surrounding Prabowo Subianto’s speeches during the 2024 political cycle. As digital interaction reshapes communication, this research moves beyond simple categorisations of hostility to explore the